OPTIMASI WAKTU EKSTRAKSI DAUN PECUT KUDA (Stachytarpheta jamaicensis) DENGAN METODE DIGESTI DAN NILAI RENDEMEN EKSTRAKNYA - Amin, asni; Risda Waris; Devita (Journal Pharma Saintika, 2025)
Abstract: Extraction of natural medicines can not only extract chemical components from the sample, but also be a guideline in determining yield value (extract). One of the extraction methods is digestion. The purpose of this research is to optimize the digestion extraction time and determine the high yield value of blue porterweed (Stachytarpheta jamaecensis) leaf extract obtained. Horse whip leaf extract (EPK) was obtained by digestion at 2 (D1), 4 (D2) and 6 (D3) hours at 40oC using 70% ethanol solvent, the ethanol extract was evaporated with a rotary vaccum-evaporator 10 degrees below its boiling point to become a thick extract. Each extract was weighed and the yield value was calculated. The results of digestion extraction obtained the yield value of EPK in D1 = 12,4%; EPK in D2 =  15,36%, and EPK in D3 = 12.3%. Extraction optimization using the digestion method can be used as a reference for the development of herbal medicines for  traditional medicine manufacturers.